An audit of ECT in England 2011–2015: Usage, demographics, and adherence to guidelines and legislation. (20th October 2017) - Read, John; Harrop, Christopher; Geekie, Jim; Renton, Julia
Abstract : Objectives: Electroconvulsive therapy (ECT) continues to be used in England, but without comprehensive national auditing. Therefore, information was gathered on usage, demographics, consent, and adherence to the guidelines of the National Institute of Clinical Excellence (N.I.C.E.) and to the Mental Health Act. Design and Methods: Freedom of Information Act requests were sent to 56 National Health Service Trusts. Results: Thirty‐two trusts provided some usable data. Only 10 were able to report how many people received psychological therapy prior to ECT in accordance with N.I.C.E. recommendations, with figures ranging from 0% to 100%. The number of people currently receiving ECT in England annually is between 2, 100 and 2, 700, and falling. There was a 12‐fold difference between the Trusts with the highest and lowest usage rates per capita. Most recipients are still women (66%) and over 60 (56%). More than a third (39%) is given without consent, with 30% of Trusts not adhering to mental health legislation concerning second opinions. At least 44% were not using validated measures of efficacy, and at least 33% failed to do so for adverse effects. Only four provided any actual data for positive outcomes or adverse effects. None provided any data on efficacy beyond the end of treatment. Conclusions: National audits should be reinstated. Independent, objective monitoring of adverse effects is urgently required. An investigation into why ECT is still administered excessively to older people and women seems long overdue. Practitioner points: Mental health staff should seek to ensure that all depressed people in their service are offered evidence‐based psychological treatments before being offered E.C.T. Staff should lobby managers to ensure proper auditing of E.C.T. within their service Individuals receiving ECT should be closely monitored for adverse cognitive effects Overuse of ECT with women and older people should be avoided